1982
DOI: 10.1002/kin.550140307
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reactions of sulfur dioxide with carbonaceous particles

Abstract: The rate of adsorption of SO2 on a prototype carbonaceous surface was measured a t low pressure in a flow reactor. The measured rate indicates a maximum atmospheric loss of SO2 hy heterogeneous reaction of l%/h for a particle density of 100 pglm". The capacity of carbon particles to adsorb SO2 is limited a t -1 rng SO? g-' C. NO:, has no effect on the rate of SO? adsorption or the saturation behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Using the reaction rate quoted above, this implies an SO 2 removal rate due to heterogeneous reaction on black carbon in the smoke plume from the Kuwait oil fires of ~ 0.1% h '1. As discussed byBaldwin [1982], most measurements of SO 2 oxidation on black carbon indicate that the surface becomes saturated when 1 was 26.5 gg m '3. If 30% of this sulfate was due to heterogeneous reaction with black carbon, this would imply that the black carbon was able to take up at least 90 mg of SO 2 per gram of black carbon, which is more than 10 times the capacity measured by Baldwin.…”
mentioning
confidence: 90%
“…Using the reaction rate quoted above, this implies an SO 2 removal rate due to heterogeneous reaction on black carbon in the smoke plume from the Kuwait oil fires of ~ 0.1% h '1. As discussed byBaldwin [1982], most measurements of SO 2 oxidation on black carbon indicate that the surface becomes saturated when 1 was 26.5 gg m '3. If 30% of this sulfate was due to heterogeneous reaction with black carbon, this would imply that the black carbon was able to take up at least 90 mg of SO 2 per gram of black carbon, which is more than 10 times the capacity measured by Baldwin.…”
mentioning
confidence: 90%
“…The secondary pollutants (SO 4 2− , NO 3 − , and NH 4 + ) in PM are photochemically converted from gases and comprise 2.4% of PM 10 and 3.7% of PM 2.5 . In particular, SO 4 2− is generated by secondary chemical reactions in the atmosphere [ 25 , 26 ], whereas NO 3 − is generated by combustion of fossil fuels [ 27 ]. When the subway service is inactive, a diesel motor car is operated to maintain the tunnel, and NO 3 − and SO 4 2− are transported from the outdoor air through the ventilation system [ 2 , 16 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fitting a Langmuir-Hinshelwood model, they found a heat of reaction 44.8 kJ/mol, with a heat of SO 2 adsorption of 27.6 kJ/mol. Baldwin [1982] measured SO2 uptake on charcoal at room temperature and found that the uptake is first order in both SO 2 concentration (3x10 -•$ to 3x10 -3 torr) and in the amount of charcoal with a maximum of about 1 mg SO 2 / g C. More recently, Molina-Sabio et al [1995] performed experiments at-10øC with SO2 partial pressures between 1 and 730 torr. In the -•1 torr range, SO2 had only weak interactions with the activated carbon surface.…”
Section: Introductionmentioning
confidence: 99%